Anticoagulation in extracorporeal membrane oxygenation - Wong, Judith Ju-Ming; Lam, Joyce Ching Mei; Mok, Yee Hui; Lee, Jan Hau (Journal of Emergency and Critical Care Medicine, 2018)
During extracorporeal membrane oxygenation (ECMO) support, the underlying disease process and contact between blood and non-biological surfaces cause alterations in haemostasis. This results in the activation of coagulation and platelet pathways and consumption of factors which can provoke haemorrhage, thrombosis or both. Currently, despite its limitations, unfractionated heparin (UFH) is the anticoagulant of choice in patients supported on ECMO. However, there is increasing experience with the use of new anticoagulants (bivalirudin, argatroban and lepirudin). Bleeding remains the most common complication and the use of haemostatic adjuncts in ECMO, including antifibrinolytic agents and desmopressin are supported by a weak body of evidence, although there is growing literature to support the cautious use of recombinant activated factor VII in certain situations. Bleeding bundles have been advocated to ensure step-by-step measures are taken to control bleeding. Similarly, advancements in monitoring of anticoagulation may lie in the development of anticoagulation laboratory protocols and algorithms. This review aims to furnish the ECMO provider with an update on advancements in anticoagulation in ECMO.